2022
DOI: 10.1038/s41420-022-00983-w
|View full text |Cite
|
Sign up to set email alerts
|

circ_0004140 promotes LUAD tumor progression and immune resistance through circ_0004140/miR-1184/CCL22 axis

Abstract: Lung adenocarcinoma (LUAD) is a highly prevalent cancer with high mortality. Immune resistance and tumor metastasis are the pivotal factors for the promotion of LUAD. CircRNAs have been revealed a crucial pre-clinical diagnostic and therapeutic potentials in LUAD. Herein, we identify a novel circRNA (circ_0004140), derived from the oncogene YAP1, which is up-regulated in LUAD. The high expression of circ_0004140 is correlated with poor prognosis and CTL cells dysfunction in LUAD patients. Knockdown of circ_000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…24 Circ_0004140 level was elevated in lung adenocarcinoma, and circ_0004140 interference suppressed lung adenocarcinoma progression via the miR-1184/CCL22. 9 Consistent with this former study, circ_0004140 abundance was found to be enhanced in lung adenocarcinoma. More importantly, circ_0004140 silencing repressed cell proliferation, migration, invasion, and angiogenesis and induced the apoptosis of lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Circ_0004140 level was elevated in lung adenocarcinoma, and circ_0004140 interference suppressed lung adenocarcinoma progression via the miR-1184/CCL22. 9 Consistent with this former study, circ_0004140 abundance was found to be enhanced in lung adenocarcinoma. More importantly, circ_0004140 silencing repressed cell proliferation, migration, invasion, and angiogenesis and induced the apoptosis of lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Circ_0000326 expression was markedly upregulated in lung adenocarcinoma, and it contributed to lung adenocarcinoma development via sponging miR‐338‐3p 24 . Circ_0004140 level was elevated in lung adenocarcinoma, and circ_0004140 interference suppressed lung adenocarcinoma progression via the miR‐1184/CCL22 9 . Consistent with this former study, circ_0004140 abundance was found to be enhanced in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most studied respiratory diseases is lung cancer, currently one of the most prevalent cancers worldwide 55 . Wang et al.…”
Section: Circrnas Regulate Ferroptosis In Diseasementioning
confidence: 99%
“…For instance, Jiang et al [3] found that lnc-REG3G-3-1/miR-215-3p facilitates brain metastasis of LUAD via manipulation of Lectin and SLC2A5. Liu et al [4] discovered that circ_0004140/miR-1184/CCL22 axis promotes the progression of LUAD through circ_0004140. In addition, it has been found that sodium selenite weakens the malignant progression of LUAD by inhibiting stemness [5], indicating that inhibiting tumor cell stemness may be one of the strategic approaches to improve the treatment of LUAD.…”
Section: Introductionmentioning
confidence: 99%